Estudio ambiental de la actividad minera artesanal no metalica, en la concesion minera Roca Blanca Sagitario, Rioja –2009 - López Flores, kathiuska Kirakú (2010)
A global, national and regional levels, the nonmetallic mineral is being exploited by informal without any permission, and is but without their respective Environmental Management Plan, bringing first loss impacts on soil, landscape aesthetics in flora and fauna and others. That is why this research study entitled "ENVIRONMENTAL STUDY OF THE NON- TRADITIONAL METAL MINING ACTIVITY IN THE WHITE ROCK MINING CONCESSION SAGITTARIUS, RIOJA -2009" town center located within the Rural, Yacu Tambo district of Rioja was developed using as relevant regulatory issues governing this activity. For the realization of the project was initially made the screening process based on the general project data, then a brief description of the project and the environmental characteristics of the environment, identifying significant environmental impacts, using the rating criteria for components affected environment, and helping to take mitigation measures proposed by the category i belonging to the project. A description of the various stages that includes the project like construction, operation, maintenance and post closure closure, then is a description of the environment variables by reference to the climate, physiography and topography, geology, geomorphology, soil and water resources. It was the identification of environmental impacts using leopold matrix components which relate to the stages of the project valuing the impacts according to the chart scale, the activity that generates the greatest impact is the stage of non-metallic mineral extraction, raw material confitillo is according to the phase of operation that allows a modification of the geomorphology, physiography, relief, gas generation and sediment particles. Concludes by proposing measures to prevent, control and mitigation, contingency plans, monitoring plan and measures of closure and post closure.